Combination of Shamir Adleman's Elgamal Rivest Algorithm and Least Significant Bit in Securing Files - Jerri Pradana Sikumbang; Sriani (Sean Institute, 2021)
The security condition of a file can be determined by means of several algorithms. So far, the identification of file security levels generally only uses the Google Drive link. Such security will take relatively fast time to be hacked by illegal data thieves and because it generally has limitations in file security. Knowing a link by the sender of the file can be retrieved by data thieves. It takes a system that is able to carry out the encryption process objectively, consistently and with clearer results. One of them is the segmentation process using the Elgamal RSA and LSB algorithms. The combination process aims to further secure the Combination of the RSA and LSB Elgamal algorithm combination files to encrypt data with more complicated calculations. From the results of data encryption into the image the sender file provides only the image, the recipient can retrieve a pdf of the image, even if the image is spread on the internet the data will be safe. Because retrieving data from the image requires the privacy key of the sender of the file and decrypts the calculation of the RSA and LSB Elgamal algorithm combination.